PERANAN AKIVATOR DAN LUAS PENAMPANG KARBON AKTIF TERHADAP KEMAMPUAN ADSORPSI KARBON AKTIF PADA MINYAK GORENG BEKAS PAKAI - Miftahul Husnah; Ridwan Yusuf Lubis; Lisa Astari (JOURNAL ONLINE OF PHYSICS, 2023)
Used oil or used cooking oil is oil that is produced from leftover frying. The high price of cooking oil and the high need for use also makes fried traders use used cooking oil continuously which has a negative impact on health. This study aims to determine the role of activators and cross-sectional area on the adsorption ability of activated carbon produced from nipa palm shells in the process of refining used oil. The sample used is used cooking oil which is then adsorbed using activated carbon with different cross-sectional areas. Analysis of the cross-sectional area shows that variations in the concentration of NaCl as an activator in the manufacture of activated carbon from nipa palm shells affect the cross-sectional area, the higher the concentration of NaCl activator, the greater the cross-sectional area of activated carbon produced. The surface area of activated carbon activated by NaCl 0M, 4M, 6M and 8M had respective values of 11.1489 m2/g, 11.4487 m2/g, 11.5028 m2/g, 11.5079 m2/g. The results show that the greater the cross-sectional area of activated carbon, the greater the ability of activated carbon to adsorb used oil, with a value of water content and volatile matter of 0.2612% - 0.1195%, peroxide of value (POV) of 11.8629 meq/g - 5.3029 meq/g, Acid Value (AV) of 1.3368 mg KOH/g - 0.5393 mg KOH/g. Optimum results were obtained on activated carbon activated with 8M NaCL activator, this was due to the increasing concentration of the activator, more pores were formed so that the absorption capacity of activated carbon also increased.